Conjugal transfer of erm(B) and multiple tet genes from Lactobacillus spp. to bacterial pathogens in animal gut, in vitro and during food fermentation. (February 2019) - Thumu, Surya Chandra Rao; Halami, Prakash M.
Abstract: Three strains of Lactobacillus comprising Lactobacillus salivarius (CHS-1E and CH7-1E) and Lactobacillus reuteri (CH2-2) previously isolated from chicken meat were analyzed for their transferability of antibiotic resistance (AR) genes to pathogenic strains under in vivo, in vitro, and during food fermentation. For in vivo model, Albino Wistar rats were inoculated with 10 10  CFU/g/ml of Enterococcus faecalis JH2-2 (recipient). After 7 days, either of two donors L. salivarius CH7-1E or L. reuteri [harbouring erythromycin and tetracycline resistance genes] were introduced at a concentration of 10 9  CFU/ml daily for 1 week. Two days after donor introduction, there was a stable increase in the number of transconjugants in the animal faeces from 10 2 to 10 3  CFU/g and presented erm (B), tet (M), tet (L) and tet (W) in their genome like donor strains. Similar observations were made with in vitro filter mating between CHS-1E, CH2-2 and CH7-1E and E. faecalis JH2-2 with transfer frequencies of 1 × 10 −4, 3.8 × 10 −3 and 2 × 10 −3 per donor cell respectively. With the results obtained in vivo and in vitro, the AR transferability of donor strains was estimated during food fermentation (chicken sausage, fermented milk or idli batter) with pathogenic recipient strains added as contaminants. At the end of mating period, phenotypic resistance to erythromycin and tetracycline in Listeria monocytogenes and Yersinia enterocolitica strains was observed. This study showed the ability of food borne Lactobacillus in diffusing their AR traits in diverse natural environments increasing their concern of AR dissemination in the food chain when used as food additives and/or probiotics. Graphical abstract: Unlabelled Image Highlights: We determined the co-existence of erm (B) and multiple tet genes and transposons on single plasmids of Lactobacillus Spp. The Lactobacillus strains could readily colonize the animal gut and transfer the resistant genes to bacterial pathogens Genetic transfer of AR in food fermentations was dependent on the survival of donor and/or the recipient strains Lactobacillus Spp. from Indian commercial meat products have food safety and public health implications